Development and simulation via flexsim for kitting trolley design of rear car seat assembly process / A.F. Sarimi ... [et al.] - Sarimi, A.F; Nasir, Nursalbiah; Rashid, H.; Azis, N. A. (Smart Manufacturing Research Institute (SMRI), 2023)
It was discovered that the material retrieval system used for a Sweden brand car seats assembly lines (RB40% and RM60%) in a local seat assembly company was not systematic in its arrangement of the assembly parts and only had a rack trolley that carried all the assembly parts in a poly-box, thus affecting the productivity. Although kitting trolleys implementation was generally known to help pre-kit earlier at logistic/warehouse department, the fabrication cost and long-term benefit would be affecting company decision to implement kitting trolley in the production line. Thus, CAE analysis for layout and process simulation specifically the kitting process would help company to determine impact of trolley implementation towards productivity. The study aims to design kitting rack specifically for RB40% and RB60% assembly line and to investigate the kitting implementation effect toward productivity through FlexSim simulation.Project started from feasibility study of existing kitting rack trolley in market to conceptual design to detailed design and simulation analysis. Detailed design of the kitting trolley was produced and from the design, time study showed that assembly process per carseat was reduced. The current Flexsim kitting trolley simulation predicted improvement of productivity could be improved from 87.5% (current practice) to 91.2% for RB60% assembly. Nonetheless, both showed improvement of hence improving of quantities hence increase company's productivity and eliminate waste of time.